Nicotine Inhalation and Suicide: Clinical Correlates and Behavioral Mechanisms. Issue 4 (9th June 2021) - Swann, Alan C.; Graham, David P.; Wilkinson, Anna V.; Kosten, Thomas R.
Abstract : Background and Objectives: Extensive evidence links smoking and suicide independently of psychiatric diagnoses, but there are questions about the pathophysiology and specificity of this relationship. We examined characteristics of this linkage to identify potential transdiagnostic mechanisms in suicide and its prevention. Methods: We reviewed literature that associated suicide with smoking and e‐cigarettes, including the temporal sequence of smoking and suicide risk and their shared behavioral risk factors of sensitization and impulsivity. Results: Smoking is associated with increased suicide across psychiatric diagnoses and in the general population, proportionately to the number of cigarettes smoked per day. Rapid nicotine uptake into the brain through inhalation of conventional cigarettes, electronic cigarettes (e‐cigarette), or even second‐hand smoke can facilitate long‐term sensitization and short‐term impulsivity. Both impair action regulation and predispose to negative affect, continued smoking, and suicidal behavior. Intermittent hypoxia, induced by cigarettes or e‐cigarettes, synergistically promotes impulsivity and sensitization, exacerbating suicidality. Two other shared behavioral risks also develop negative urgency (combined impulsivity and negative affect) and cross‐sensitization to stressors or to other addictive stimuli. Finally, early smoking onset, promoted by e‐cigarettes in never‐smokers, increases subsequent suicide risk. Conclusion and Scientific Significance: Prevention or cessation of nicotine inhalation can strategically prevent suicidality and other potentially lethal behavior regardless of psychiatric diagnoses. Medications for reducing smoking and suicidality, especially in younger smokers, should consider the neurobehavioral mechanisms for acute impulsivity and longer‐term sensitization, potentially modulated more effectively through glutamate antagonism rather than nicotine substitution. (Am J Addict 2021;30:316–329)